Aflatoxin B1: Toxicity, bioactivation and detoxification in the polyphagous caterpillar Trichoplusia ni. (16th January 2013) - Zeng, Ren Sen; Wen, Zhimou; Niu, Guodong; Berenbaum, May R.; Zhu‐Salzman, Keyan
Abstract Trichoplusia ni caterpillars are polyphagous foliage‐feeders and rarely likely to encounter aflatoxin B1 (AFB1), a mycotoxin produced by Aspergillus flavus and A. parasiticus, in their host plants. To determine how T. ni copes with AFB1, we evaluated the toxicity of AFB1 to T. ni caterpillars at different developmental stages and found that AFB1 tolerance significantly increases with larval development. Diet incorporation of AFB1 at 1 μg/g completely inhibited larval growth and pupation of newly hatched larvae, but 3 μg/g AFB1 did not have apparent toxic effects on larval growth and pupation of caterpillars that first consume this compound 10 days after hatching. Piperonyl butoxide, a general inhibitor of cytochrome P450 monooxygenases (P450s), reduced the toxicity of AFB1, suggesting that AFB1 is bioactivated in T. ni and this bioactivation is mediated by P450s. Some plant allelochemicals, including flavonoids such as flavones, furanocoumarins such as xanthotoxin and imperatorin, and furanochromones such as visnagin, that induce P450s in other lepidopteran larvae ameliorated AFB1 toxicity, suggesting that P450s are also involved in AFB1 detoxification in T. ni.